Handbook of brewing (CRC/Taylor & Francis, 2006)
The Handbook focuses on recent developments in brewing, such as hops and novel hop products, brewhouse technology, process control in the brewhouse, packaging technology, and approaches to maintaining beer quality. It describes traditional and obscure beer styles such as chocolate and coffee-flavored beers. It discusses key areas of modern brewing science and includes chapters on microbreweries and the future of brewing. Exploring the future of brewing, this edition also describes new avenues to challenge the brewer's art of manufacturing a quality beverage from barley-based raw materials